Respon jaringan periodontal terhadap penggunaan nikel kromium sebagai komponen gigitiruan cekat - Ardiansyah S. Pawinru; Edy Machmud (DiscoverSys Inc., 2009)
The use of fixed partial denture (FPD) nowdays has been very popular in our society.This is due to their smaller size, and more convenient to be used and fixed in themouth. The choice of nickel chromium (NiCr)as the metal component of FPD isbased on its character of corrosion proof, light, and hard. However, nickel containedcan be allergic. Allergic reactions reported, vary from oedema of tongue and lip, andmouth lining until anaphylaxis. These reactions are related to the pattern andcorrosion modes, followed by the release of metalic ions like nickel into the oralcavity. This depends not only on the composition of metal, but also the temperatureand pH of the oral cavity. Some studies have reported the use of NiCr might causeinflammation reaction of periodontal tissue.